2020
DOI: 10.1016/j.jpba.2020.113107
|View full text |Cite
|
Sign up to set email alerts
|

Combination of intact, middle-up and bottom-up levels to characterize 7 therapeutic monoclonal antibodies by capillary electrophoresis – Mass spectrometry

Abstract: Significant growth of biopharmaceuticals requires powerful analytical methods to better understand their structure by establishing a complete characterization. To this end, a combination of bottom-up, middle-up and intact molecule levels with a capillary electrophoresis-mass spectrometry coupling has been performed to have a comprehensive picture of monoclonal antibodies. In this study, 7 worldwide health authorities approved mAbs have been analyzed to get information about their charge heterogeneity, the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…The off-line sample preparation comprising a digestion and reduction steps can be performed within one hour, and requires a low amount of material (104). The 25 kDa fragments can then be easily separated by LC (107)(108)(109) or CE (110)(111)(112)(113) and simultaneously identified by HRMS instruments such as QTOFs and Orbitrap analyzers that can resolve the isotopic pattern of 25kDa proteins with a mass accuracy around 5 ppm. The middledown approach, which refers to MS/MS-based experiments, can also be performed for sequencing these fragments (114).…”
Section: Middle-up Analysis 31 Conventional Middle-down/up Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The off-line sample preparation comprising a digestion and reduction steps can be performed within one hour, and requires a low amount of material (104). The 25 kDa fragments can then be easily separated by LC (107)(108)(109) or CE (110)(111)(112)(113) and simultaneously identified by HRMS instruments such as QTOFs and Orbitrap analyzers that can resolve the isotopic pattern of 25kDa proteins with a mass accuracy around 5 ppm. The middledown approach, which refers to MS/MS-based experiments, can also be performed for sequencing these fragments (114).…”
Section: Middle-up Analysis 31 Conventional Middle-down/up Analysismentioning
confidence: 99%
“…Several studies highlighted the advantages of combining the analysis of antibodies at multiple levels, i.e. intact, reduced, middle-up, and peptide level, to allow a fast and extensive characterization (111,(131)(132)(133). For instance, Giorgetti et al reported the combination of intact, middle-up, and bottom-up analysis using a CE-MS instrument for the analysis of 7 FDA-approved mAbs(111) with: i) the identification of major N-glycoforms at the intact level; ii) additional PTMs as K-clip, oxidations or deamidations observed at the middle-up level; and iii) a precise location and relative quantitation of each PTM at the bottom-up level.…”
Section: Automated Middle-up Analysis and Multi-level Characterizationmentioning
confidence: 99%
“…The applicability of CE-MS in PTM analysis was demonstrated with seven commercial therapeutic antibodies [62]. The method was used to identify glycoforms and other PTMs, especially low mass PTMs, using intact, middle-up, and bottom-up approaches.…”
Section: Primary Sequence and Ptm Analysismentioning
confidence: 99%
“…The presence of major glycoforms, that is, 2xglycosylated and 1x-glycosylated isoforms, in seven commercially available mAbs was recently analyzed in less than 12 min using CE-MS of intact and IdeS digested forms [62]. Glycosylation analysis has also been reported via relative quantification of N-glycans at the glycopeptide level [68].…”
Section: Primary Sequence and Ptm Analysismentioning
confidence: 99%
“…Proteomics should ideally be the driver for improving diagnostics and will serve as a primary method for detection of molecular changes indicative of disease states. Numerous laboratories have reported a plethora of assays using capillary electrophoresis in conventional format and in microfluidic format for detection and quantification of several proteoforms [254][255][256][257][258][259][260][261][262][263][264][265][266][267]. However, in order for proteoforms to reach their full clinical potential, it is necessary to be able to accurately detect and quantify near all proteoforms in biological fluids using advanced and sophisticated analytical instrumentation, such as IACE.…”
Section: Future Of Immunoaffinity Capillary Electrophoresis For the Analysis Of Proteoformsmentioning
confidence: 99%